Antioxidant and Antimicrobial Potential of Hydroethanolic Extracts of Padina tetrastromatica from North-west Coast of India - Layana, P.; Martin Xavier, K. A.; Lekshmi, S.; Deshmukhe, Geetanjali; Nayak, B. B.; Balange, Amjad K. (Fishery Technology, 2019)
Brown seaweeds are rich sources of several biologically active compounds, particularly polyphenols. The present study investigates the efficiency of hydroalcoholic solvent to extract bioactive molecules from the brown seaweed P. tetrastromatica. Six different combinations of ethanol in water (0, 20, 40, 60, 80 and 100% v/v) mixture were employed to extract the bioactives with an objective to study their antioxidant and antimicrobial activity. The antioxidant potential of different extracts was assessed by Total Phenolic Content (TPC), Ferric-reducing antioxidant power (FRAP) assay, 1,1-diphenyl-2- picrylhydrazyl (DPPH) radical scavenging activity, 2, 2’-azino-bis 3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical cation scavenging and Total antioxidant activity assays. 100% ethanolic extract was found to have the highest TPC and exhibited significantly higher antioxidant activity for all tests done while aqueous extract contained the highest extractive yield. The antimicrobial activity of the extracts were also evaluated against food spoilage and pathogenic bacteria using disc diffusion assay. 100% extracts significantly (p<0.05) inhibited the growth of gram-negative bacteria while 60% extract also exhibited the best inhibitory effects against gram-positive bacteria. HR-LCMS analysis of the extracts revealed that 100% ethanolic extract contained a higher number of alkaloid compounds than phenolic compounds whereas aqueous extracts contained more phenolic compounds. It was observed that as the polarity decreases, the efficiency of a hydroethanolic solvent to extract active alkaloid compounds along with polyphenols increases, which in turn contributes to the higher bioactivity of the extract.